The Counsellor as a Stress Management Consultant to School Staffs - Van Hesteren, Frank (Canadian Journal of Counselling and Psychotherapy, 2012)
It is maintained in this article that the counsellor can make a valuable contributio nto school staffs in the role of a stress management consultant. Possible stress management workshop components are described and guidelines are provided for consultation in a school setting. An attempt is made to familiarize prospective and practicing counsellors with recent literature, research, and resource materials that can make up the knowledge and activity bases of stress management consultation.